Association Between Literacy Status and Wellbeing of Elderly People Living in Old Care Homes in Kathmandu - Adhikari, Min Raj; Acharya, Anuradha (Education Quarterly, 2024)
Ageing induces multidimensional changes in an individual’s well-being, demanding extensive care. In Nepal, shifting structure from a joint to a nuclear family, reduced fertility and increasing outmigration pose challenges in elderly care. This study examines the impact of literacy status on the physical and mental well-being of elderly people residing in old care homes. The data was collected from sixty purposively selected participants aged 60 and above using standardized tools (GDS-15 and EQ-5D-5L). The analysis of data was performed using SPSS version 20. Results reveal a significant association between literacy and well-being. The literate group reported better general health and lower levels of depression compared to the illiterate group. These findings underscore the importance of literacy in enhancing the overall well-being of elderly individuals.